PELATIHAN COREL DRAW DI MTS NURUL IMAN KARANGANYAR - Imam Hidayat; Wahyu Nugroho; Andi Wapa (Yayasan Bakti Cendekia Nusantara, 2025)
This service aims to provide an understanding of Corel Draw. The community service activities socialized by the Bakti Indonesia University in Dawuhan Wetan Village are a form of effort to practice the Tri Dharma of Higher Education, namely Community Service. This effort was carried out during the world pandemic that is currently hitting Indonesia. Including Dawuhan Wetan Village, Rowokangkung District, Lumajang Regency. In responding to and helping residents in facing the new normal era, especially in the field of Informatics Engineering, the author applies and demonstrates a form of training process that is easy to understand and easy to understand. The target aspect targeted by the author is children who go to junior high school, with various methods of reviewing field results that are considered very necessary for guidance and introduction. The author found a problem, namely the lack of knowledge of MTS NURUL IMAN students in Karanganyar 1 hamlet in technology. So from this problem, the author provides guidance and introduction to technology which aims to help junior high school children get to know technology better.